Investigation on food packaging polymers: Effects on vegetable oil oxidation. (15th June 2020) - Hu, Keqing; Huyan, Zongyao; Ding, Shaoxuan; Dong, Yaoyao; Yu, Xiuzhu
Highlights: Contact form between packaging and vegetable oil was simulated and evaluated. Hydrophilicity of materials is related to the hydroperoxide production in oil. PE surfaces can promote oil hydroperoxide decomposition into volatile products. Abstract: Polyethylene (PE), polypropylene (PP), polyamide (PA), and polyethylene terephthalate (PET) surfaces and particles were employed to study effects of polymer materials on linseed oil, peanut oil, rapeseed oil and sunflower seed oil oxidation. The surface types of the materials, hydroperoxide content and volatile in oils were determined by contact angle, Fourier transform infrared spectroscopy and gas chromatography-mass spectrometry. Oils on PP surfaces underwent a more rapid oxidation, followed by PA, PE and PET. Except PP sets, this order was consistent with surface hydrophilicity of polymers. Further study using polymer particles avoiding packaging barrier suggested this was probably due to barrier factors. Although PE surfaces allowed oil to have lower content of hydroperoxides, it can promote oil hydroperoxide decomposition into volatile products. Surface types of polymer materials are correlated with oxidation of contacted oil, and these surfaces can also affect the oil secondary oxidation and the degradation of oxidation products.